Life and death [compact disc, unabridged] : Twilight reimagined - Meyer, Stephenie, 1973- (The Twilight saga, 2015)
A reimagining of Twilight with reversed gender roles. In the new book, Bella is Beau, and Edward is now Edythe. All other characters are the opposite genders as well, with the exception of Charlie and Renee.